Time and frequency domain causality Testing: The causal linkages Revisited betweenFiscal Policy and Economic Growth in Pakistan - Iqbal, Sidra; Irshad, Maryam; Yasmeen, Najma; Yasmin, Fouzia (The journal of contemporary issues in business and government, 2021)
Research on the impact of fiscal policy is a dire need in today’s economic world. In this investigation, fiscal policy effectson economic growth have been explored.In this analysis,the researcher examined the relationships using the secondary data source for the 1972-2019 data series by employing Auto-Regressive Distributed Lagged Model (ARDL) and frequency domain causality Testing to investigate the causal linkages between Fiscal Policy and Economic Growth in Pakistan. The variables have been used as the budget deficit and economic growth as the core variables of theresearch and concluded the negative association between the fiscal policy (budget Deficit) and economic growth.